722 Heterogeneity in the Diagnosis of Coeliac Disease in Paediatric Patients. (October 2012) - Croaker, D; Swann, J; Hallam, L; Jenkins, P; Beardsley, C
Abstract : Background: "Gluten intolerance" is commonly diagnosed and often confused in the public mind with coeliac disease. Authors in Western Australia recently demonstrated an approximately 5% rate of coexistence of eosinophilic oesophagitis (EO) with villous atrophy. We asked whether our population was similar. Methods: We performed a retrospective chart review of all those with gastroscopy and small-bowel biopsy and a subsequent diagnosis of CD in children less than 16 years of age between 1 April 2003 and the 31st of June 2011. Main results: 239 gastroduodenoscopies were reviewed. Biopsy of both the oesophagus and duodenum was available in 231 patients. There were 124 patients positive for coeliac disease, 105 negative, and 10 indeterminate. 14 of 231 were positive for EO, and 4 of the 126 CD patients were also positive for EO. Two of the four CD + EO patients were rescoped during the time interval, and both were in remission for changes of CD, although both still had changes of EO evident. There were 7 CD patients reported with other forms of oesophageal inflammation. Histologically of our four patients with EO and villous atrophy, at least three have potentially allergic changes instead of full-blown CD. Conclusion: There have been recent suggestions that serological and other tests may render the small bowel biopsy unnecessary in the management of CD. We note that EO is associated with villous atrophy in 3 to 4% cases. Serology and symptomatology presenting as coeliac disease continues to warrant detailed investigation, including endoscopic work up.